A Theory of Currency Unions and Equity Price Shocks - Warburton, Christopher E.S. (Journal of Reviews on Global Economics, 2017)
This paper investigates the effects of financial shocks on per capita national income of multiple currency unions in different geographic locations. Though exposure to financial market shock is hardly considered and not generally measured as an important convergence criterion for unionization, currency unions are generally formed to attain greater regional and global economic integration. As a general theory, this paper finds that shocks to equity prices have imprecise implications for the performance of currency unions with divergent sources of income, different currency arrangements, evolutionary trade alliances, and unequal financial exposure. Specifically, historical alliances, geographic proximity, or even union membership, may not provide sufficient explanation for income volatility in currency unions after an exposure to equity price shocks. By utilizing annual time series data without seasonal adjustments to decompose variances, this paper finds that changes in equity prices may not significantly account for the volatility in per capita income of currency unions with weak intra-union trading patterns and less stringent currency arrangements.